Natural Killer Cells in Kidney Health and Disease - Turner, Jan-Eric; Rickassel, Constantin; Healy, Helen; Kassianos, Andrew J. (Frontiers in Immunology, 2019)
Natural killer (NK) cells are a specialised population of innate lymphocytes that have a major effector function in local immune responses. While their immunological functions in many inflammatory diseases are well established, comparatively little is still known about their roles in kidney homeostasis and disease. Our understanding of kidney NK cells is rapidly evolving, with murine studies highlighting the functional significance of NK cells in acute and chronic forms of renal disease. Recent progress has been made in translating these murine findings to human kidneys, with indications of NK cell subset-specific roles in disease progression in both native and allograft kidneys. Clearly, a better understanding of the molecular mechanisms driving NK cell activation and importantly, their downstream interactions with intrinsic renal cells and infiltrating immune cells is necessary for the development of targeted therapeutics to halt disease progression. In this review, we discuss the properties and potential functions of kidney NK cells.